Analysis of factors that influence young farmers' interest in entrepreneurship in the agribusiness sector in Batu City, East Java, Indonesia - Costa, Fidel Da; Arvianti, Eri Yusnita; Santosa, Budi (Fakultas Pertanian Universitas Yudharta Pasuruan, 2025)
Introduction: Agriculture is the primary source of livelihood for people throughout the world. The agricultural sector plays an important role in national development and cannot be separated from various problems. Agribusiness is an approach that can be used in agricultural development activities. Efforts to increase young farmers' interest in the agricultural sector by exploring the factors that encourage interest in farming. The aim of this research is to determine the factors that influence young farmers' interest, and the factors that most dominantly influence young farmers' interest in entrepreneurship in the agribusiness sector. Methods: This research was conducted in Batu City, from October-November 2023. This research used primary and secondary data. The sample taken was 97 respondents. The sampling technique used in this research was the accidental sampling method. Data were analyzed using Structural Equation Modeling (SEM). Results: The research results show that factors that influence the interest of young farmers are; individual character, family environment, non-family environment, land area, economy, and motivation. The factors studied have a significant influence both directly and indirectly through motivation on young farmers' interest in entrepreneurship in the agribusiness sector. Among them, the land area factor which has the most dominant influence contributes equally to the interest of young farmers in entrepreneurship in the agribusiness sector in Batu City. Conclusion: This research concludes that all the factors studied have a significant influence both directly and indirectly through motivation on young farmers' interest in entrepreneurship in the agribusiness sector. Among them, the land area factor which has the most dominant influence contributes equally to the interest of young farmers in entrepreneurship in the agribusiness sector in Batu City.